Immuno-qPCR analysis and immunogenicity assessment of next generation oligonucleotides and their targeted delivery molecules - Suomi, Fanni (My University, 2020)
Biotherapeutic products (BTPs) are therapeutics often made by genetically engineered organisms such as living bacterial or mammalian cells. BTPs enable effective and targeted treatment for several chronic and life-threatening diseases. Recently, nucleic acid-based therapeutics such as oligonucleotides and small interfering RNAs have gained interest as they can be used to inhibit or induce gene expression. The potentially reduced toxicity of oligonucleotide therapeutics could offer a safer alternative to currently available drugs. However, the safety trials of these novel BTPs need to adapt to the new needs of the industry, and this lays new claims to novel pharmacokinetic analyses and immunogenicity methods. The aim of this study was to develop a pharmacokinetic quantitative immuno polymerase chain reaction (qIPCR) assay for next generation oligonucleotide therapeutics and their targeted delivery molecules. The qIPCR assay deploys a ligand-binding assay (LBA) in the extraction of oligonucleotide-protein conjugates from serum samples. The detection of the oligonucleotide was carried out by qPCR. Additionally, a proof of concept Anti-drug antibody (ADA) bridging assay was developed for the assessment of immunogenicity. A solid phase oligonucleotide-protein conjugate was used as capture molecule to bind antibodies which were detected with Eu3+ chelate-labeled oligonucleotide-protein conjugates by DELFIA (dissociation-enhanced lanthanide fluorescent immunoassay) technology. The sensitivity of the developed ADA bridging assay was 248 ng/mL and the cut point of the assay was 1.10 at 5 % false positive rate. The developed qIPCR method needs further optimization due to deviation between replicate samples which is caused by the LBA phase of the assay. The sensitivity of the ADA bridging assay meets the regulations for pre-clinical studies. However, if the ADA bridging assay is applied to a clinical study, the sensitivity needs to be improved.
Keywords: Biotherapeutic products, pharmacokinetics, immunogenicity, safety assessment